Pemetaan Arena Kerja Menggunakan Sensor Ultrasonik Pada Robot Omnidireksional - Sendari, Siti; Fajar Syahputra, Alief; Nurutami, Amalia; Kartika Sari, Elista; Agus Rahma Dani, Ayunda; Desti Yanti, Dava (Jurnal FORTECH, 2020)
In this research, robot omnidirectional is designed for mapping area work. The omnidirectional robot has has a mechanical design that is different with the usual wheels. These wheels are designed to make the robot has an ability to move in Omni directions. With this system, the movement of the robot will have 2 degrees of freedom which can move on the x axis and the y axis. The Omni wheel consists of large core wheels and small wheels around the circumference of the wheels. This robot can avoid obstacles and map the arena by using ultrasonic sensors (HC-SR04). The robot designed and developed in this study is aimed to map the arena with an area of one square meter in the form of a two-dimensional (2D) space map. The distance readings are displayed on a 20x4 LCD screen by using the HC-SR04 ultrasonic sensor. The robot is controlled via an Arduino Mega microcontroller. The omnidirectional wheels is used as a mean of motion. Based on the results of the robot testing of the sensor readings, the actuators and mapping work well. It can be seen on how they can avoid obstacles by turning left or right by displaying the readings from the ultrasonic sensor